2021
DOI: 10.1007/s00432-021-03662-y
|View full text |Cite
|
Sign up to set email alerts
|

The ability of post-chemoradiotherapy DWI ADCmean and 18F-FDG SUVmax to predict treatment outcomes in head and neck cancer: impact of human papilloma virus oropharyngeal cancer status

Abstract: Objectives To evaluate the ability of post-chemo-radiotherapy (CRT) diffusion-weighted-MRI apparent diffusion coefficient (ADCmean) and 18F-FDG PET maximum standardized uptake value (SUVmax) to predict disease-free survival (DFS) in head and neck squamous cell carcinoma (HNSCC), and to determine whether this ability is influenced by human papillomavirus oropharyngeal cancer (HPV-OPC) status. Methods This prospective cohort observational study included 65 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 57 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…Twenty-eight studies with a total of 2634 patients (1571 HPV+ cases, 899 HPV− cases), conducted between 2014 and 2022, were included in this review. Fourteen out of twenty-eight studies used MRI to find differences between HPV+ and HPV− patients ( Table 1 ) [ 2 , 19 , 20 , 25 , 28 , 29 , 35 , 38 , 39 , 41 , 43 , 47 , 49 , 50 ], the other studies aimed to predict HPV status using MRI ( Table 2 ) [ 21 , 22 , 23 , 26 , 27 , 31 , 32 , 37 , 40 , 42 , 44 , 45 , 46 , 48 ]. The main findings from each feature category are summarized in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-eight studies with a total of 2634 patients (1571 HPV+ cases, 899 HPV− cases), conducted between 2014 and 2022, were included in this review. Fourteen out of twenty-eight studies used MRI to find differences between HPV+ and HPV− patients ( Table 1 ) [ 2 , 19 , 20 , 25 , 28 , 29 , 35 , 38 , 39 , 41 , 43 , 47 , 49 , 50 ], the other studies aimed to predict HPV status using MRI ( Table 2 ) [ 21 , 22 , 23 , 26 , 27 , 31 , 32 , 37 , 40 , 42 , 44 , 45 , 46 , 48 ]. The main findings from each feature category are summarized in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The main findings from each feature category are summarized in Table 3 . Twenty-one studies had a retrospective cohort study design [ 2 , 19 , 20 , 21 , 22 , 25 , 26 , 28 , 29 , 31 , 32 , 35 , 37 , 38 , 39 , 42 , 44 , 45 , 47 , 48 , 49 ], and seven studies had a prospective cohort study design [ 23 , 27 , 40 , 41 , 43 , 46 , 50 ]. Of the twenty-eight included papers, five papers focused on structural MRI sequences that were used in routine clinical examinations [ 19 , 20 , 21 , 22 , 23 ], nineteen focused on DWI sequences [ 2 , 25 , 27 , 28 , 29 , 31 , 32 , 35 , 36 , 38 , 39 , 41 , 42 , 44 , 45 , 46 , 47 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 97,111,157,158 For example, Connor et al found HNSCC patients with higher post-treatment ADC mean values 6 and 12 weeks following RT were associated with increased 2 year disease free survival rates. 158 At 6 weeks, an optimum threshold of 1405 10 –6 mm 2 /s was derived (with a sensitivity of 83%, specificity of 80%, PPV of 39% and NPV of 97%) and at 12 weeks an optimum threshold of 1840 10 –6 mm 2 /s was derived (with a sensitivity of 83%, specificity of 57%, PPV of 22% and NPV of 96%). 158 …”
Section: Early Post-treatment Imagingmentioning
confidence: 99%
“… 158 At 6 weeks, an optimum threshold of 1405 10 –6 mm 2 /s was derived (with a sensitivity of 83%, specificity of 80%, PPV of 39% and NPV of 97%) and at 12 weeks an optimum threshold of 1840 10 –6 mm 2 /s was derived (with a sensitivity of 83%, specificity of 57%, PPV of 22% and NPV of 96%). 158 …”
Section: Early Post-treatment Imagingmentioning
confidence: 99%